Contactin‐6‐deficient male mice exhibit the abnormal function of the accessory olfactory system and impaired reproductive behavior. Issue 4 (1st March 2023) - Zhang, Wei; Huang, Huiling; Gui, Ailing; Mu, Di; Zhao, Tian; Li, Hongtao; Watanabe, Kazutada; Xiao, Zhicheng; Ye, Haihong; Xu, Yiliang
Abstract: Introduction: Contactin‐6 (CNTN6), also known as NB‐3, is a neural recognition molecule and a member of the contactin subgroup of the immunoglobulin superfamily. Gene encoding CNTN6 is expressed in many regions of the neural system, including the accessory olfactory bulb (AOB) in mice. We aim to determine the effect of CNTN6 deficiency on the function of the accessory olfactory system (AOS). Methods: We examined the effect of CNTN6 deficiency on the reproductive behavior of male mice through behavioral experiments such as urine sniffing and mate preference tests. Staining and electron microscopy were used to observe the gross structure and the circuitry activity of the AOS. Results: Cntn6 is highly expressed in the vomeronasal organ (VNO) and the AOB, and sparsely expressed in the medial amygdala (MeA) and the medial preoptic area (MPOA), which receive direct and/or indirect projections from the AOB. Behavioral tests to examine reproductive function in mice, which is mostly controlled by the AOS, revealed that Cntn6 −/− adult male mice showed less interest and reduced mating attempts toward estrous female mice in comparison with their Cntn6 +/+ littermates. Although Cntn6 −/− adult male mice displayed no obvious changes in the gross structure of the VNO or AOB, we observed the increased activation of granule cells in the AOB and the lower activation of neurons in the MeA and the MPOA as compared with Cntn6 +/+ adult male mice. Moreover, there were an increased number of synapses between mitral cells and granule cells in the AOB of Cntn6 −/− adult male mice as compared with wild‐type controls. Conclusion: These results indicate that CNTN6 deficiency affects the reproductive behavior of male mice, suggesting that CNTN6 participated in normal function of the AOS and its ablation was involved in synapse formation between mitral and granule cells in the AOB, rather than affecting the gross structure of the AOS. Abstract :